Evolving Wallerian degeneration after transient retinal ischemia in mice characterized by diffusion tensor imaging - Sun, Shu-Wei; Liang, Hsiao-Fang; Cross, Anne H.; Song, Sheng-Kwei (NeuroImage (Orlando, Fla.), 2008)
Wallerian degeneration plays a significant role in many central nervous system (CNS) diseases. Tracking the progression of Wallerian degeneration may provide better understanding of the evolution of many CNS diseases. In this study, a 28-day longitudinal in vivo DTI of optic nerve (ON) and optic tract (OT) was conducted to evaluate the temporal and spatial evolution of Wallerian degeneration resulting from the transient retinal ischemia. At 3–28 days after ischemia, ipsilateral ON and contralateral OT showed significant reduction in axial diffusivity (32–40% and 21–29% respectively) suggestive of axonal damage. Both ON and OT showed significant increase in radial diffusivity, 200–290% and 58–65% respectively, at 9–28 days suggestive of myelin damage. Immunohistochemistry of phosphorylated neurofilament (pNF) and myelin basic protein (MBP) was performed to assess axonal and myelin integrities validating the DTI findings. Both DTI and immunohistochemistry detected that transient retinal ischemia caused more severe damage to ON than to OT. The current results suggest that axial and radial diffusivities are capable of reflecting the severity of axonal and myelin damage in mice as assessed using immunohistochemistry.